The mediating role of family dynamics in the relationship between paternal incarceration and child behavior problems - Antle, Kelsey (Journal of crime and justice, 2020)
While many scholars acknowledge that there are collateral consequences of mass incarceration, there remains considerable work to be done in understanding the nuanced way in which paternal incarceration influences child development. A growing body of research has begun examining the specific mechanisms through which a father’s time in jail or prison might influence child behavior. Using data from the Fragile Families and Child Wellbeing Study, this study examines maternal depression, maternal parenting stress, paternal involvement, and spanking as potential mediators in the relationship between paternal incarceration and child behavior problems. Results indicate that paternal incarceration exerts a persistent direct effect on child externalizing behaviors (i.e., aggression, rule-breaking), and an indirect effect on both externalizing and internalizing behaviors (i.e., withdrawal, anxiety, and somatic disorders) via parenting mechanisms, even after controlling for pre-incarceration levels of mechanisms and child behavior problems. The limitations of this study and directions for future research are discussed.